Inovasi Pembelajaran Berbasis Folklor untuk Meningkatkan Identitas Budaya: Studi Etnografi di PKBM Sanggar Lingkaran - Junaidi Junaidi; Rahmat Rahmat; Sri Whayuni Tanshzil (Paedagogi: Jurnal Kajian Ilmu Pendidikan (e-journal), 2026)
This study aims to analyze the implementation of folklore-based learning at PKBM Sanggar Lingkaran and its contribution to strengthening learners’ cultural identity. The study employed a qualitative method with an ethnographic approach. Data were collected through one month of participant observation using a live-in strategy, in-depth interviews with 13 informants consisting of the PKBM head, administrators, educators, and educational staff, as well as document analysis. Data were analyzed using Spradley’s ethnographic model and supported by ATLAS.ti software. The findings reveal that folklore is integrated into the learning process through oral, partly oral, and non-oral folklore manifested in the Paloh Naga folktale, Malay poems and pantun, performing arts, traditional games, cultural rituals, traditional attire, and local culinary practices connected to Paloh Naga Agro-tourism and Pasar Kamu. The ethnographic findings indicate that learners’ direct engagement in community cultural practices promotes the internalization of cultural values, strengthens their sense of belonging to local culture, and fosters character development, creativity, and social skills. The study contributes by proposing an empirical model of folklore-based learning that positions culture as a living learning resource within community-based education, thereby extending the discourse on cultural identity strengthening in nonformal education.